Hi,

G = grandpa's age

D = dad's age

B = brother's age

G + D + B = 85

G - 3 = 2*(D - 3)

D + 4 = 4*(B + 4)

Three equations with three variables. Can you do the next step?

Results 1 to 3 of 3

- Oct 19th 2009, 09:27 AM #1

- Joined
- Sep 2006
- Posts
- 134

- Oct 19th 2009, 09:36 AM #2

- Joined
- Oct 2009
- Posts
- 11

- Oct 19th 2009, 11:06 AM #3

- Joined
- Jan 2008
- From
- Big Stone Gap, Virginia
- Posts
- 2,550
- Thanks
- 15
- Awards
- 1

Hi reiward,

Let's do it with one equation....for fun.

**Let x = dad's age**

2(x-3)= grandpa's age -3

**2(x-3)+3 = grandpa's age**

x + 4 = 4(brother's age +4)

x + 4 = 4 (brother's age) +16

**(x - 12)/4 = brother's age**

Now, add 'em up.

x + 2(x-3)+3+(x-12)/4 = 85

x + 2x-6+3 + (x-12)/4 = 85

4x + 8x - 12 + x - 12 = 340

13x = 364

**x = 28 (Dad's age)**

**2(x-3)+3 = 2(28-3)+3 = 2(25)+3 = 53 (Grandpa's age)**

**(x-12)/4 = (28-12)/4 = 16/4 = 4 (Brother's age)**